Regional differences in cellular mechanisms of adipose tissue gain with overfeeding - Tchoukalova, Yourka D; Votruba, Susanne B; Tchkonia, Tamara; Giorgadze, Nino; Kirkland, James L; Jensen, Michael D (Proceedings of the National Academy of Sciences - PNAS, 2010)
Body fat distribution is an important predictor of the metabolic consequences of obesity, but the cellular mechanisms regulating regional fat accumulation are unknown. We assessed the changes in adipocyte size (photomicrographs) and number in response to overfeeding in upper- and lower-body s.c. fat depots of 28 healthy, normal weight adults (15 men) age 29 ± 2 y. We analyzed how these changes relate to regional fat gain (dual energy X-ray absorptiometry and computed tomography) and baseline preadipocyte proliferation, differentiation [peroxisome proliferator-activated receptor-γ2 (PPARγ2) and CCAAT/enhancer binding protein-α (C/EBPα) mRNA]), and apoptotic response to TNF-α. Fat mass increased by 1.9 ± 0.2 kg in the upper body and 1.6 ± 0.1 kg in the lower body. Average abdominal s.c. adipocyte size increased by 0.16 ± 0.06 μg lipid per cell and correlated with relative upper-body fat gain (r = 0.74, P < 0.0001). However, lower-body fat responded to overfeeding by fat-cell hyperplasia, with adipocyte number increasing by 2.6 ± 0.9 × 10(9) cells (P < 0.01). We found no depot-differences in preadipocyte replication or apoptosis that would explain lower-body adipocyte hyperplasia and abdominal s.c. adipocyte hypertrophy. However, baseline PPARγ2 and C/EBPα mRNA were higher in abdominal than femoral s.c. preadipocytes (P < 0.005 and P < 0.03, respectively), consistent with the ability of abdominal s.c. adipocytes to achieve a larger size. Inherent differences in preadipocyte cell dynamics may contribute to the distinct responses of different fat depots to overfeeding, and fat-cell number increases in certain depots in adults after only 8 wk of increased food intake.